Procedural Skills Training in Emergency Medicine Physicians Within the Edmonton Zone: A Needs Assessment. Issue 2 (11th July 2020) - Schonnop, Rebecca; Stauffer, Brandy; Gauri, Aliyah; Ha, David
Abstract: Objectives: The objectives were to describe the current procedural skill practices, attitudes toward procedural skill competency, and the role for educational skills training sessions among emergency medicine (EM) physicians within a geographic health zone. Methods: This is a multicenter descriptive cross‐sectional survey of all EM physicians working at 12 emergency departments (EDs) within the Edmonton Zone in 2019. Survey items addressed current procedural skill performance frequency; perceived importance and confidence; current methods to maintain competence; barriers and facilitating factors to participation in a curriculum; preferred teaching methods; and desired frequency of practice for each procedural skill. Results: Survey response rate was 53.6%. Variability in frequency of performed procedures was seen across the type of hospital sites. For the majority of skills, there was a significantly positive correlation between the frequency at which a skill was performed and the perceived confidence performing said skill. There was inconsistency and no significant correlation with perceived importance, perceived confidence or frequency performing a given skill, and the desired frequency of training for that skill. Course availability (76.2%) and time (72.8%) are the most common identified barriers to participation in procedural skills training. Conclusions: This study summarized the current ED procedural skill practices among EM physicians in the Edmonton Zone and attitudes toward an educational curriculum for procedural skill competency. This represents a step toward targeted continuing professional development in staff physicians.